Organizational behavior improving performance and commitment in the workplace - Colquitt, Jason; LePine, Jeffery A.; Wesson, Michael J. (New York, NY McGraw-Hill Education, 2019)
"Organizational Behavior 6th edition by Colquitt, LePine, and Wesson continues to offer a novel approach using an integrative model and roadmap to illustrate how individual, team, leader, and organizational factors shape employee attitudes, and how those attitudes impact performance and commitment. This model reminds students where they are, where they've been, and where they're going. They include two unique chapters on job performance and organizational commitment. Those topics are critical to managers and students alike, and represent critical outcomes in OB. Each successive chapter then links back to those outcomes, illustrating why OB matters in today's organizations"
PART 1 INTRODUCTION TO ORGANIZATIONAL BEHAVIOR: What Is Organizational Behavior? -- Job Performance -- Organizational Commitment -- PART 2 INDIVIDUAL MECHANISMS. Job Satisfaction -- Stress -- Motivation -- Trust, Justice, and Ethics -- Learning and Decision Making -- PART 3 INDIVIDUAL CHARACTERISTICS. Personality and Cultural Values -- Ability -- PART 4 GROUP MECHANISMS. Teams: Characteristics and Diversity -- Teams: Processes and Communication -- Leadership: Power and Negotiation -- Leadership: Styles and Behaviors -- PART 5. ORGANIZATIONAL MECHANISMS -- Organizational Structure -- Organizational Culture.
Revised edition of the authors' Organizational behavior, [2016].
Machine generated contents note: PART 1 INTRODUCTION TO ORGANIZATIONAL BEHAVIOR CHAPTER 1: What Is Organizational Behavior? CHAPTER 2: Job Performance CHAPTER 3: Organizational Commitment PART 2 INDIVIDUAL MECHANISMS CHAPTER 4: Job Satisfaction CHAPTER 5: Stress CHAPTER 6: Motivation CHAPTER 7: Trust, Justice, and Ethics CHAPTER 8: Learning and Decision Making PART 3 INDIVIDUAL CHARACTERISTICS CHAPTER 9: Personality and Cultural Values CHAPTER 10: Ability PART 4 GROUP MECHANISMS CHAPTER 11 Teams: Characteristics and Diversity CHAPTER 12 Teams: Processes and Communication CHAPTER 13 Leadership: Power and Negotiation CHAPTER 14 Leadership: Styles and Behaviors PART 5 ORGANIZATIONAL MECHANISMS CHAPTER 15: Organizational Structure CHAPTER 16: Organizational Culture.
Prof. Sia (Recommending faculty) - Bookfair 2019
Includes bibliographical references and indexes.
Keywords: Organizational behavior; Personnel management; Strategic planning; Consumer satisfaction; Job satisfaction